Aurah covering parameters: a study on Muslim women's level of understanding - Hasmad, Nurjannah; AlOsman, Abdulrahman (Penerbit Universiti Sultan Zainal Abidin, 2021)
Islam emphasizes preserving chastity onto its believers, which is derived into several commandments to achieve this goal. Among them is aurah (parts of body that are prohibited to be exposed to the public) covering. In the context the current society, wearing a hijab (veil) among female Muslim is a common sight in public places. However, wearing a hijab is not what all it takes to completely cover the aurah, in fact, one may wear the hijab but with tight-fitting clothes, for example, that does not adhere to the right concept of aurah covering. This article aims to investigate the level of understanding on aurah covering parameters among Muslim women. Quantitative analysis has been conducted for 135 female students from 27 different nationalities in the International Islamic University Malaysia where a questionnaire consisting of questions related to aurah covering parameters are distributed. Datas were analysed using the SPSS version 26. The findings suggest that Muslim women have a high level of understanding on aurah covering parameters. The findings from this study may be helpful in providing insights to further exploration of hijab and aurah covering issue as there have not yet many studies tackling the hijab issue from the perspective of aurah covering guidelines.